JThermodynamicsCloud: Cloud-based tool for temperature dependent thermodynamic calculations using group additivity rules and data management - Edward S. Blurock (Case Studies in Chemical and Environmental Engineering)
JThermodynamicsCloud, as its predecessors JThermodynamics, JTherGas and TherGas, use a dataset of fundamental data, such as Benson rules, the HBI method, symmetry corrections, steric corrections, ring strain and nearest neighbor interactions, to calculate the temperature dependent thermodynamics from 2D-graphical species representations of molecules and radical species needed for combustion modelling of (large) reaction mechanism, both hand and machine generated. JThermodynamicsCloud differs from previous versions in that it is cloud-based Software as a Service (SaaS) with improved data-management that promotes FAIR (that data is Findable, Accessible, Interoperable and Reuseable) data practices and the concepts of data lineage and traceability. Of particular note is that all database updates can be traced to source data and different sets of fundamental data can be configured for the final calculation. The emphasis of this paper will be to describe the state of the art design features promoting data lineage, provenance, traceability, transparency, and FAIR data practices that make JThermodynamicsCloud a unique system for the management of (thermodynamic and chemical) data. The data, database structure, database organization, the use of ontologies and the concept of transactions will be described in the context of promoting state of the art database management practices. The techniques outlined here are particularly useful for calculations where several sets of information are combined to perform a calculation and where the data is continually being updated. The description of the specific group additivity thermodynamic calculations methods is left to previous papers. Though the system described involves the calculation of thermodynamic quantities, the data management principles and system structure described goes well beyond this case study and can be applied to a multitude of further applications.